(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Irregularities in buildings are always expected due to many reasons like aesthetics, light, ventilation, etc. The irregularity is due to the reason the stiffness center and mass center of the building is not at the same location. Hence it is needed to study behavior of such structures during earthquake. The objective of this study is to understand plan irregularity and to analyze the seismic performance of the irregular frame using nonlinear static analysis in SAP2000. The study includes identification and measure of the irregularity level due to the irregular plan and improvement of the structural system considering seismic behavior.